Diagnostic Criteria of Postoperative Cognitive Dysfunction: A Focused Systematic Review - Kim van Sinderen; Lothar A. Schwarte; Patrick Schober (Anesthesiology Research and Practice)
Postoperative Cognitive Dysfunction (POCD) is characterized by a deterioration in cognitive performance after surgery and is increasingly addressed in research studies. However, a uniform definition of POCD seems to be lacking, which is a major threat to clinical research in this area. We performed a focused systematic review to determine the current degree of heterogeneity in how POCD is defined across studies and to identify those diagnostic criteria that are used most commonly. The search identified 173 records, of which 30 were included. Neurocognitive testing was most commonly performed shortly before surgery and at 7 days postoperatively. A variety of neurocognitive tests were used to test a range of cognitive domains, including complex attention, language, executive functioning, perceptual-motor function, and learning and memory. The tests that were used most commonly were the Mini-Mental State Examination, the digit span test, the trail making test part A, and the digit symbol substitution test, but consensus on which test result would be considered “positive” for POCD was sparse. The results of this systematic review suggest the lack of a consistent approach towards defining POCD. However, commonalities were identified which may serve as a common denominator for deriving consensus-based diagnostic guidelines for POCD.